2017
DOI: 10.1016/j.jcol.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile and clinical characteristics of patients with intestinal inflammatory disease

Abstract: According to several epidemiological studies, there is a significant increase in cases of inflammatory disease in developing countries. Objective To describe epidemiological data and clinical features of patients with inflammatory bowel disease in patients enrolled in Campo Grande, MS. Method A retrospective descriptive study with a database analysis of patients who were enrolled and renewed their process in the Exceptional Medications Program of the Health Department from January 2008 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
1
12
0
14
Order By: Relevance
“…In 11 studies, the greatest proportion of patients had extensive (pancolitis). 10 , 17 , 21 24 , 27 – 30 , 33 In a nationwide study in Mexico, which separated UC extension by age group, pancolitis was the most frequent extension of UC in children (64.4%), adult (62.2%) and elderly (57.7%) patients; distal/proctosigmoiditis was the second most frequent extension in children (22.2%), adult (24.8%) and elderly (26.8%) patients; and left-sided colitis was the least frequent extension in children (13.3%), adult (13.0%) and elderly (15.6%) patients. 27 , 28 In line with this, the highest proportion of patients (43%) had pancolitis in a study in Argentina.…”
Section: Resultsmentioning
confidence: 99%
“…In 11 studies, the greatest proportion of patients had extensive (pancolitis). 10 , 17 , 21 24 , 27 – 30 , 33 In a nationwide study in Mexico, which separated UC extension by age group, pancolitis was the most frequent extension of UC in children (64.4%), adult (62.2%) and elderly (57.7%) patients; distal/proctosigmoiditis was the second most frequent extension in children (22.2%), adult (24.8%) and elderly (26.8%) patients; and left-sided colitis was the least frequent extension in children (13.3%), adult (13.0%) and elderly (15.6%) patients. 27 , 28 In line with this, the highest proportion of patients (43%) had pancolitis in a study in Argentina.…”
Section: Resultsmentioning
confidence: 99%
“…Dos resultados analisados, em relação a distribuição dos diagnósticos entre os espectros da DII, houve maior proporção de DC na população estudada, discordando do perfil epidemiológico de pacientes do Espírito Santo e de outros estados do Brasil, onde a prevalência de RCU é maior (63,84%) (3,14) . A amostra estudada foi concordante com perfis epidemiológicos do território brasileiro quanto à prevalência por sexo, maior em mulheres (61,5%) (4,13) .…”
Section: Discussionunclassified
“…A incidência possui um padrão bimodal, atingindo tanto adultos jovens, dos 20 aos 40 anos, quanto idosos a partir dos 55 anos. Acomete predominantemente indivíduos brancos e tem distribuição similar em ambos os sexos, com prevalência aumentada no sexo feminino na DC (4) .…”
Section: Introductionunclassified
“…[50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD. [24] The larger case-series in LAC Countries are from 1946 to date are from Argentina [14,51,52], Barbados [13], Brazil [14,[53][54][55][56][57][58][59][60][61][62][63][64][65], Chile [66][67][68], Cuba [69], Peru [70,71], Puerto Rico [72][73][74][75] and Uruguay. [76][77][78] Most CD localizations were ileal-colonic and CD behavior was mostly inflammatory, followed by penetrant or stenotic.…”
Section: Discussionmentioning
confidence: 99%